Clinical hypertension - Kaplan, Norman M; Lieberman, Ellin; Neal, William W (Williams & Wilkins, 1998)
Univ. of Texas Southwestern, Dallas. Brandon/Hill Medical List selection. Comprehensive reference for practitioners. Previous edition: c1994. DNLM: Hypertension.
Keywords: kardiologie; Hypertension; angiologie; hypertenze